PEMBELAJARAN SEJARAH MELALUI MODEL GALLERY WALK - HERLINA HERLINA (IAI DDI POLEWALI MANDAR, 2023)
The purpose of this study was to improve students' abilities in learning history through the application of the gallery walk learning model with the formulation of the problems: (a) What are the efforts to increase the activity of students in the subject of the Indonesian National Resistance against the Dutch East Indies Government by applying the gallery walk learning model? (b) How to increase learning outcomes by applying the gallery walk learning model? The subjects of this study were 23 students in class XI IBB 2. Qualitative data obtained through observation and quantitative data collected from written tests. The results of this study indicate an increase in activity. The average score of students in cycle 1 was 75.34 and in cycle 2 was 80. Student completeness in cycle 1 was 69.56% and cycle II was 86.95%.